A kistérségek gazdasági és társadalmi jellemzői és trendjei Észak-Dunántúlon - Szörényiné Kukorelli, Irén (Tér és Társadalom, 1997)
The essay is based on the former delimitation of the small regions of Nortwest Transdanubia. The basis of the delimitation was the physical geographical, historical and ethnographic information in the questionnaires coming from the settlements. Instead of the delimitation of the Central Statistical Agency, which divided the region into 27 small regions, a more subtle region divided into 48 small regions is now analysed. At the level of the small regions, the method of cluster and factor analysis was selected to analyse the socio-economic characteristics. Having chosen seven groups of characteristics, namely demography, structure of the labour force, infrastructure, general economic activity, industry, agriculture and tourism, and processing each of the small regions with the method of cluster and factor analysis, the small regions were put into groups. Finally, after the summary of the results, different clusters of small regions were defined. From the point values of the small regions, we can clearly draw three different stripes of the developed regions in the spatial structure of the region: A northern stripe with a nortwest-southeast direction, covering the small regions of Mosonmagyaróvár and Győr. A western border stripe, which comprises the Sopron, the Csepreg-Bük, Kőszeg and Szombathely region. The southern edge of the region is clearly visible, reaching from the Zalaegerszeg small region, through Little Balaton, the Keszthely-Hévíz Mountains and along the Lake Balaton and through the Várpalota area, to the border of the region. We can find, however, the so-called "depression basin" of the region, covering the border areas of Vas, Veszprém and Zala counties. The Vasvár, Jánosháza, Sümeg, Zalaszentgrót, Zalakaros small regions and the Somló area are part of this depression region.